Ginger essential oil-loaded hydrogels: preparation, characterization, cytotoxicity, antimicrobial and anti-inflammatory activity - Arpa, Muhammet Davut; Kesmen, Ebrar Elif; Arslan, Tugba; Karadag, Ayse Esra; Biltekin, Sevde Nur; Demirci, Fatih (Taylor & Francis Inc, 2024)
The present study aimed to develop ginger essential oil hydrogel formulations, using sodium carboxymethyl cellulose (Na CMC), Carbopol, and xanthan gum for dental and oromucosal infections. The physicochemical properties of the hydrogels were evaluated, and their bioadhesive characteristics were determined. Antimicrobial activity, cytotoxicity, and lipoxygenase (LOX) inhibitory activities of the essential oil and its formulations were investigated, respectively. The major components of ginger essential oil were confirmed as alpha-zingiberene (39.0%) and ar-curcumene (23.7%) by GC-FID and GC/MS analyses. The initial results showed that none of the tested gel formulations selected for the application were non-cytotoxic. According to antimicrobial and LOX enzyme activity studies, the essential oil-loaded xanthan gum gel (X3) was more effective compared to the essential oil itself. The initial formulation and biological evaluation studies concluded that ginger essential oil hydrogels (X3, C3) can be further developed for oral and dental health by providing a long residence time due to their bioadhesive properties.
Keywords: Zingiber officinale; hydrogel; formulation; antimicrobial; anti-inflammatory